Synergizing Mobile POS and Social Commerce: Case Study of Toko Isa Sembako, Bandar Lampung: Sinergi Mobile POS dan Perdagangan Sosial: Studi Kasus Toko Isa Sembako, Bandar Lampung - Isyiffah Putri; Lina Fatimah Lishobrina (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
The digital infrastructure gap has forced the majority of traditional grocery wholesalers in Indonesia, who still rely on manual record keeping to face intense pressure from modern retailers. This qualitative case study examines whether the integration of Mobile POS (Qasir), WhatsApp Business, and Instagram on the QRIS platform can build digital resilience and operational efficiency at Toko Isa Sembako in Bandar Lampung. Through interviews with five informants, three weeks of observation, and analysis based on the UTAUT/UTAUT2, SWOT, and 5P frameworks, it was found that Toko Isa had only recently digitized its payment process via QRIS GoPay Merchant. Although aware of the benefits of Qasir, the owner was hindered by poor connectivity, staff limitations, and the burden of adapting to new habits. The SWOT matrix identified these operational gaps as the most critical internal weaknesses. As a solution, the 5P strategy establishes the adoption of Qasir as the first step, as POS data serves as the factual foundation for determining products, prices, and promotions in social commerce. This low-cost synergy demonstrates that the combination of Mobile POS and social media offers a practical path to long-term business resilience through regular training, which simultaneously has tangible implications for SME digital inclusion policies